Analytical method development of pitavastatin-loaded SNEDDS formulation: Multivariate analysis regarding ultraviolet spectrophotometry analysis - Kuncahyo I; Choiri S; Fudholi A; Abdul Rohman; Ronny Martien (Journal of Food and Pharmaceutical Sciences, 2019)
Herein, this work aimed to develop and assess feasibility of multivariatemodel of partial least square analysis for specific quantification ofpitavastatin (PVT)-loaded self-nano emulsion (SNE) formulation using UVVis spectrophotometry.PVT loaded into self-nano emulsion formulation comprising of Capryol-90, Tween 80, and Transcutol P under different loading levels i.e. 10-90mg/mL. All samples scanned using UV-Vis spectrophotometer from 300-200nm. PVT and SNE were prepared separately for estimation of interference.Multivariate model was constructed using partial least square (PLS)regression analysis as well as principal component analysis for qualitativepattern recognition. Cross-validation using a leave one out technique andgoodness of fit parameters were applied for model evaluation.The results revealed that maximum sensitivity of PVT was obtained at 244nm. SNE formulation had different interference value and decreasedexponentially as increasing the PVT loading in the SNEDDS formulation. Thehighest drug loading had an interference value of 7.11%. Therefore, theSNEDDS formulation interfered the PVT quantification and mainlydepended on the drug loading. Finally, multivariate analysis, PLS could beapplied to eliminate the placebo/formulation interference for PVTquantification independently towards drug loading level.